2020
DOI: 10.1186/s41702-020-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the cell population and wound healing-related gene expression in deep partial-thickness burn wound model

Abstract: Background: Burns are injuries that lie on the skin or other organic tissues caused by exposures to the heat, electricity, chemicals or ionizing radiation. The present study was carried out to record temporal changes in the cell population and wound healing-related gene expression in rats with deep partial-thickness burn. Methods: Burn wound was induced on the dorsal part of Sprague-Dawley rats using temperature-regulated 20-mm wide aluminum head heating device. Animals were then sacrificed on days three, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…A moderate increase in MMP-9 serum concentration is beneficial because the epithelialization rate is partially dependent on the presence of collagen. However, when the physiological balance between protease and their inhibitors is broken, the patient outcome is unfavorable (9). Our results showed an early increase in the MMP-9 level, most likely due to its rapid release from neutrophil granulocytes, over minutes to a few hours after the triggering insult (P1, 1744.19 ng/ml vs. C, 279.36 ng/ml, P<0.001).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A moderate increase in MMP-9 serum concentration is beneficial because the epithelialization rate is partially dependent on the presence of collagen. However, when the physiological balance between protease and their inhibitors is broken, the patient outcome is unfavorable (9). Our results showed an early increase in the MMP-9 level, most likely due to its rapid release from neutrophil granulocytes, over minutes to a few hours after the triggering insult (P1, 1744.19 ng/ml vs. C, 279.36 ng/ml, P<0.001).…”
Section: Discussionmentioning
confidence: 64%
“…Simultaneously, the decrease in TIMPs leads to intense matrix proteolysis (5)(6)(7)(8). Virtually, any imbalance between MMPs and TIMPs may lead to low healing processes such as chronic wounds or excessive healing, including hypertrophic scars and keloids (9).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showing an increasing trend for TIMP-1 are in contrast to other studies (11,23) that have found significantly higher TIMP-1 concentrations in the plasma of patients with TBSA affected by a burn of <20% relative to healthy controls, with a median time to peak TIMP-1 concentration at 2.09 days. Given that a moderate increase in the MMP-9 serum concentration is beneficial, the epithelialization rate being partially dependent on the presence of collagen (13,16), MMP-9 levels remaining constant during the 7-day monitoring period could be associated with a better-quality scar. Because none of the patients enrolled in our study had septic complications during the 7-day monitoring period, the maintaining/decrease of MMP-9 serum levels may be an indicator for better survival.…”
Section: Discussionmentioning
confidence: 99%
“…In burn wounds, with a typical chronic evolution, degradation products can be found but it is not clear which of the tissue proteinases are responsible for local repair (10). Another possible explanation could be the degradation of the adhesion molecules and growth factors by the local proteinases (12)(13)(14). Moreover, the expression of different tissue proteases in burn wounds could influence the prognosis (15).…”
Section: Role and Dynamics Of Matrix Metalloproteinase 9 And Tissue Inhibitor Of Metalloproteinase 1 In Burn Patientsmentioning
confidence: 99%
“…Burns are a very common skin injury. Depending on the depth of thermal damage, burns are divided into three main categories: superficial burns, which affect only the epidermis, partial-thickness burns, in which both the epidermis and dermis are affected, and burns of full-thickness skin (Guo et al, 2020). Deep thermal burns are characterized by the development of general and local disorders that lead to a complex of interconnected processes in all body systems (Vaghardoost et al, 2019;Sterling & Lombardi, 2021).…”
Section: Introductionmentioning
confidence: 99%